Permanent tremor reduction during thalamic stimulation in multiple sclerosis. Issue 4 (30th September 2010) - Thevathasan, Wesley; Schweder, Patrick; Joint, Carole; Ray, Nicola; Pretorius, Pieter; Gregory, Ralph; Aziz, Tipu
Abstract : Background: Unlike thalamic lesioning, thalamic stimulation is considered a reversible treatment for tremor. However, tremor in multiple sclerosis (MS) can sometimes permanently improve during thalamic stimulation. Such 'permanent tremor reduction' (PTR) has been attributed to limb weakness preventing tremor expression. In this study, 11 consecutive patients with MS tremor treated with thalamic stimulation were assessed for PTR. Eighteen upper limbs had tremor, of which 16 received contralateral stimulation. Methods: Tremor severity and limb strength were assessed preoperatively, early postoperatively (within 1 year) and late postoperatively (after 3 years). Tremor severity was rated using validated clinical scales both on and off stimulation. Following explantation, the parenchyma surrounding three electrode tracts was examined with MRI. Results: At final review (mean 5.2 years) PTR was evident in 11 of the 18 upper limbs with tremor. PTR often rendered stimulation redundant. PTR could occur when limb strength was conserved and could arise remotely from the initial surgery. PTR was significant (and universal) in limbs that received long-term (>2 years) effective (tremor suppressing) stimulation. PTR was not a significant finding in limbs that had not received long-term, effective stimulation. Contralateral to a limb with PTR, MRI revealed a thalamic lesion adjacent to the electrode tract. Thalamic lesions were not identified contralateral to two limbs without PTR. Conclusions: MS tremor often permanently improves during thalamic stimulation, even when limb strength is conserved. PTR may simply reflect natural history. Alternatively, these findings appear consistent with the recent proposal that thalamic stimulation in MS might promote local 'demyelinative lesioning.'